FAKTOR-FAKTOR PSIKOSOSIAL YANG MENYEBABKAN GANGGUAN KESEHATAN MENTAL PEKERJA PADA KLINIK PRATAMA BUNDA MEDIKA KAMPAR - NINGSIH, INDAH SUCI; Ariani, Peny (Jurnal Kajian Kesehatan Masyarakat, 2024)
This research aims to identify the psychosocial factors causing mental health disorders among employees at the Bunda Medika Pratama Clinic in Kampar. The research design used is a quantitative survey with a cross-sectional study design. The sample in this study consists of 30 employees of the Bunda Medika Pratama Clinic in Kampar, Riau Province, obtained through census sampling. Data analysis uses univariate analysis to describe the psychosocial factors causing mental health disorders. Bivariate analysis is used to determine the influence of each factor, while multivariate analysis is used to identify the dominant variables affecting mental health disorders. The results of this study reveal a significant relationship between workplace demands and the level of mental health disorders. There is no significant relationship between organizational work and job content variables and mental health disorder variables. There is a significant relationship between interpersonal relationships and leadership variables and mental health disorder variables. There is a significant relationship between interfacing with individuals and mental health disorder variables. There is no significant relationship between workplace values and mental health disorder variables. There is a significant relationship between health and well-being variables and mental health disorder variables. Furthermore, there is a significant relationship between offensive behavior variables and mental health disorder variables. Overall, offensive behavior is the dominant variable influencing mental health disorders.